Microalloying effects in ternary Cu-Zr-X (X = Be, Mg, Al, Si, P, Nb, Ag) icosahedral clusters and super-clusters from Density Functional Theory computations. (5th September 2017) - Bokas, G.B.; Lekka, Ch.E.; Papageorgiou, D.G.; Evangelakis, G.A.
Graphical abstract: A small topological change at the systems results in hybridizations with different type of electrons at the high energies. Charge transfer found from s to p and from d to p for the cases of Be and Ag dopant respectively resulting in Free of Bond planes even at the superclusters. Abstract: We present Density Functional Theory calculations results on ternary Cu8 Zr4 X icosahedral-like clusters and Cu11 Zr6 X2 superclusters, the dominant structural units of the Cu-rich eutectic metallic glass (Cu64 Zr36 ), doped with X = Be, Mg, Al, Si, P, Nb, Ag. It came out that the presence of p electrons in both 13-atom clusters and superclusters (provided from the p electron type doping elements or, effectively, in other types of dopants via charge transfer from s to p and also from d to p electrons) induces at certain energies Free-of-Bond planes. These Free-of-Bond planes could be viewed as analogs of slip planes increasing the ductility of the system. Moreover, we found that Zr atoms contribute with T2g or Eg electrons, occurring upon small topological alterations, which affect the Electronic Density of States, especially near the Fermi energy, thus permitting stress releasing. In addition, clusters with the dopant at the shell exhibit lower binding energies than those with the dopant at the center of a cluster. However, the differences in the binding energies are small, indicating that in metallic glasses these conformations may coexist and transform easily from one type of cluster to another, resulting in low energetic cost local atomic rearrangements.